Existence of solution for a fractional differential system on the chemical graph of glycerol - Li, Lishuang; Zhang, Xinguang; Chen, Peng; Wang, Ying; Wu, Yonghong (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we study the chemical graph for an important polyalcoholic compound with the molecular formula C3H8O3 by using 0 or 1 to label the elements of its molecular structure graph and formulating the corresponding fractional boundary value problem on each edge of the graph. Under the sense of Caputo’s fractional derivatives, the existence of solutions of the fractional boundary value problem on the glycerol graph is investigated by introducing some suitable growth conditions and combing with some fixed point theorems. A specific example is given to verify our results.